Hubungan Status Gizi dengan Perkembangan Kognitif Anak Usia 5-6 Tahun - Linda Dwi Pitriani; Ridha Nirmalasari; Muzakki Muzakki (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2021)
The relationship between nutritional status and cognitive development in children and toddlers, including those in the nutritionally vulnerable group. Lack of nutrition in children and toddlers can cause weakness, decreased concentration and slowed child development. The purpose of this study are to determine the relationship between nutritional status and cognitive development of children aged 5-6 years in RA Hidayatul Insan Palangka Raya. The research method used was quantitative research with a correlational approach, the method used was an analytic survey. The sample in this study were 25 students with a sampling method, namely used total sampling, where all populations were sampled. Research data collection techniques used observation, questionnaires and interviews. Data analysis used product moment correlation test. The results showed that the calculation of the product moment correlation test found that the relationship between body mass index and children's cognitive development was significantly smaller than the alpha value or 0.009 <0.05. In the relationship between upper arm circumference and child development with a significant value smaller than the alpha value or 0.024 <0.05, thus Ha was accepted, the correlations of -0.512 and -0.449. The conclusion was that there was a very weak relationship between nutritional status and cognitive development of children aged 5-6 years in RA Hidayatul Insan Palangka Raya.